Modifications of conventional organic membranes with photocatalysts for antifouling and self-cleaning properties applied in wastewater filtration and separation processes: A review - Nguyen, Hieu Trung; Pham, Minh-Thuan; Nguyen, Truc-Mai Thi; Bui, Ha Manh; Wang, Ya-Fen; You, Sheng-Jie (Separation science and technology, 2022)
The combination of conventional organic membranes and photocatalysts has led to an extensively studied field that is so-called photocatalyst modified membranes with antifouling, self-cleaning properties under UV or visible light irradiation. However, most of the research is limited to laboratory scale and artificial experimental conditions because this field still faces obstacles to practical applications. The main problems are the stability of these photocatalytic membranes or the binding between the photocatalysts and the membranes, and the low antifouling performance under visible light irradiation. Therefore, photocatalyst designs, membrane modification and fabrication methods are the key factors determining the success or failure of these photocatalytic membranes in water and wastewater filtration and separation processes. In this review, various types of photocatalyst incorporation into polymeric membranes were discussed, including the long-term stability, the organic pollutants' degradation efficiency, and the antifouling, self-cleaning performance of photocatalytic membranes. In addition, the mechanisms of membrane fouling and antifouling, membrane classifications, and fabrication methods were also discussed.